The impact of a stress‐reducing protocol on the quality of pre‐anaesthesia in cats. (1st March 2021) - Argüelles, Juan; Echaniz, Mónica; Bowen, Jonathan; Fatjó, Jaume
Abstract: Introduction: Transport to the clinic is a major source of stress for cats. The process involves being put into a carrier, driven in a car and handled. Cats are therefore removed from the safe‐haven of their territory and experience many stressful stimuli and interactions. Methods: In the present study, 31 cats were transported to the clinic following a low‐stress transport protocol and compared with a control group of 36 cats whose owners did not follow the protocol. This protocol involved preparing a cat carrier basket with F3 pheromone and keeping it covered and stable during the car journey from the home to the clinic. Pre‐anaesthesia information was recorded for cardiac rate, respiratory rate, tolerance to handling, time for sedation to be achieved and dose of propofol required for induction and endotracheal intubation. Results: The group exposed to the low‐stress transport protocol took less time to reach sedation and needed a lower dose of propofol for induction than the control group. Conclusion: These results suggest that, in cats, pre‐anaesthetic and induction requirements are influenced by lower‐stress transport and handling.